Meningkatkan Hasil Belajar Siswa Melalui Problem Based Learning pada Materi Perempuan dan Laki-Laki Diciptakan Sebagai Citra Allah Kelas V SD Negeri 3 Nainggolan - Risno Veronika Manurung (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The purpose of this study was to improve student learning outcomes through Problem Based Learning on the material Women and men are created as the image of God in class V of SD Negeri 3 Nainggolan. This study involved 12 students as participants in two cycles of action using the Problem Based Learning (PBL) method. This classroom action research uses a spiral approach, which consists of four steps of repeated unity, namely planning, acting, observing, and reflecting. Data were analyzed using quantitative descriptions. The results of the study indicate that the application of the problem based learning method has a positive impact on improving learning outcomes and the activeness of students in learning Catholic religious education and character education. The Problem Based Learning Learning Model has been proven effective in creating an interesting, active learning environment and providing more optimal learning outcomes. This study provides an important contribution in developing more effective learning strategies and can be a reference for teachers and researchers in improving student learning outcomes.